Identification of Brugia malayi immunogens by an immunoproteomics approach - Sirichit Wongkamchai (2018)
Filariasis remains a health problem in tropical countries. Identification of immunogens from its causative organism would lead to development of a better diagnostic test, as well as vaccine discovery to effectively prevent this disease. We applied immunoproteomics to define potential immunogens of adult Brugia malayi that were recognized by IgM, IgG1 and IgG4 in sera of patients with four distinct clinical spectra of filariasis, including endemic asymptomatic, lymphangitis, elephantiasis and microfilaremia (n= 5/group). Sera of healthy individuals (n= 5) from non-endemic area served as the negative control. Brugian proteins were resolved by 2-DE and subjected to 2-D Western blot analysis probed with these sera. A total of 30 immunoreactive proteins recognized by IgM, IgG1 and IgG4 in sera from all four filarial groups were identified by Q-TOF MS and MS/MS analyses. Interestingly, only three immunogens were recognized by IgM in lymphangitis, elephantiasis and microfilaremia, but not in endemic asymptomatic group. IgG1 recognized 20 immunogens in endemic asymptomatic, lymphangitis and microfilaremia (mostly in endemic asymptomatic group), but not in elephantiasis, whereas IgG4 recognized 28 immunogens in all four filarial groups (mostly in microfilaremia). This large data set is an important resource for further development of a new diagnostic test and/or vaccine for filariasis. © 2011 Elsevier B.V.